Examining the complexity of child marriage as sexual violence in digital era - Sudirman, Sudirman; Ramadhita, Ramadhita; Bachri, Syabbul; Duran, Büşra Nur (Legality : Jurnal Ilmiah Hukum, 2023)
Child marriage in the digital era is an interesting fact because this type of marriage is classified as sexual violence. However, child marriage is very common in Indonesia because of many factors. Child marriage in the digital era is known to have triggered many problems, such as reproductive health problems, domestic violence, and divorce. However, considering child marriage as a criminal offense of sexual violence (TPKS) as stated in Law Number 12 of 2022, is unwise. Departing from this issue, this research identifies three reasons why child marriage cannot be categorized as sexual violence in the digital era. The results of this paper show that child marriage in Indonesia is inevitable due to three main arguments: Islamic teachings permit child marriage, the high number of marriage dispensations, and the TPKS Law focuses more on protecting women, not the spouses of child marriage perpetrators. Another cause of child marriage is poor education in the digital era, coupled with poor understanding of the importance of self-protection from promiscuity in the digital era among community members. Education on gender equality and reproduction also has not been properly applied. Finally, marriage guidance for teenagers and prospective brides in the digital era has not been implemented yet.